Survey of community privacy in social network - Zhongyuan JIANG; Xianyu CHEN; Jianfeng MA (网络与信息安全学报)
Community is an important feature of social network and the development of community detection technology brings the danger of privacy disclosure to network users.How to protect sensitive community information from being leaked and ensure the security of users and communities has become a research hotspot in the field of network security.In recent years, community privacy protection technology has made initial progress, but there is a few survey on the research of community privacy or community security in social networks, and it may limit the potential and long-term development of this research topic.The research on the privacy of community structure was mainly reviewed and the related works on community security were classified, summarized, compared.The hot issues of community security in the future were proposed.